Grundlage für eine Humangeographie des relationalen Weltbildes. Die sozialwissenschaftliche Bedeutung von Sprachpragmatik, Ökologie und Evolution - Zierhofer, Wolfgang (ERDKUNDE, 1997)
If human geography is to be understood as a discipline which is dedicated to the study of the relations between human beings and their environment, then there is a need to adopt contributions and approaches of other disciplines into this field. This paper brings two lines of argumentation together and demonstrates their relevance for geography. The first line deals with the language pragmatics version of action theory, which is located in the overlapping areas of ethics and sociology. It will be presented as a further development of those approaches of action theory which hitherto have been taken up by geography. This establishes a social scientific base for the second line of argumentation. There are in particular contributions from the wide field of the philosophies of nature, environment and ecology relying on arguments from evolution theory and ecology, which encourage one to switch to a relational world-view. An acceptance of the core arguments implies the necessity to scrutinize the compatibility of the social scientific foundations of Geography (and other disciplines related to the environment) with the relational world-view. The language pragmatics action theory proves to be open for relational thinking, allthough the notion of society for example (used by other social scientific approaches in a similar way) has to be reformulated. This paper shows the direction in which such revisions of basic terms and concepts must be undertaken, and it concludes with a discussion of the likely consequences for geography, for other disciplines and for society.